Clinical-epidemiological peculiarities of acute respiratory infections in children from 3 to 12 years and evaluation of effectiveness of antivirus therapy - S. A. Khmilevskaya; N. I. Zryachkin; V. E. Mikhailova (Журнал инфектологии, 2019)
The aim: to study the etiological structure of acute respiratory infections in children aged 3 to 12 hospitalized in the early stages of the disease in the department of respiratory infections of the children’s hospital, and to reveal the features of their clinical course and the timing of DNA / RNA elimination of respiratory viruses from nasal secretions, depending on the method of therapy. Materials and methods: 100 children with acute respiratory infections aged 3 to 12 years were monitored. The nasal secrets on the DNA / RNA of respiratory viruses were studied by PCR. Depending on the method of therapy, patients were divided into 2 groups: patients of group 1 (comparison) received basic treatment (without the use of antiviral drugs), in patients of the 2nd group (main), along with basal therapy, the drug was used umifenovir in a 5-day course at the ageappropriate dosage. Results: In the etiologic structure of ARVI in children from 3 to 12 years, the leading place was taken by rhinovirus, influenza and metapneumovirus infections (isolated – 18%, 19% and 20% respectively, in the form of a mixed infection – 11%). The main syndromic diagnosis at the height of the disease was rhinopharyngitis. Complications were observed in 42% of cases, as often as possible with flu – 53% of cases. Features of metapneumovirus infection in children of this age group were: predominance of non-severe forms of the disease in the form of acute fever with symptoms of rhinopharyngitis, as well as a small incidence of lower respiratory tract infections. The use of the drug umiphenovir in children with acute respiratory viral infections of various etiologies contributed to significantly faster elimination of viral DNA / RNA from the nasal secretion, which was accompanied by a ecrease in the duration of the main clinical and hematological symptoms of the disease, a decrease in the incidence of complications, and reduced the duration of stay in hospital. Conclusion: application of modern molecular genetic methods of diagnostics made it possible to identify the leading role of influenza, metapneumovirus and rhinovirus infections in the etiology of acute respiratory viral infection in patients aged 3 to 12 years, and to determine a number of clinical features characteristic of this age group. The results of the study testify to the effectiveness of umiphenovir in the treatment of children with acute respiratory viral infections of various etiologies and allow us to recommend this drug as an effective and safe etiotropic agent.